2016
DOI: 10.1002/asjc.1306
|View full text |Cite
|
Sign up to set email alerts
|

New Stabilization of Continuous‐Time Delayed Systems Based on Partially Delay‐Dependent Controllers

Abstract: In this paper, a new approach is developed to discuss the stabilization problem for a class of continuous-time delayed systems, which is firstly achieved by a kind of partially delay-dependent controller. The main property of the desired controller is that both non-delay and delay states are contained. Different from the traditional stabilization methods realized by totally non-delay or delay state feedback controllers, both non-delay and delay states are contained but take place asynchronously, where the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Due to page limit and the process similar to the former situation, the corresponding computed matrices are omitted here, where only the maximum allowable delay τmax is given. In detail and similar to the above comparisons, one could get the maximum allowable delay τmax based on Corollary 3 being τmax=1.06, while τmax based on References 41,42 is τmax=0.83 and smaller. Moreover, based on Lyapunov function (65), one could also get the maximum allowable delay τmax=0.93.…”
Section: Numerical Examplementioning
confidence: 71%
See 3 more Smart Citations
“…Due to page limit and the process similar to the former situation, the corresponding computed matrices are omitted here, where only the maximum allowable delay τmax is given. In detail and similar to the above comparisons, one could get the maximum allowable delay τmax based on Corollary 3 being τmax=1.06, while τmax based on References 41,42 is τmax=0.83 and smaller. Moreover, based on Lyapunov function (65), one could also get the maximum allowable delay τmax=0.93.…”
Section: Numerical Examplementioning
confidence: 71%
“…By investigating the references as much as possible, it is found that no reference can be directly applied to the considered problems in this article. In order to make some possible and suitable comparisons and via considering lots of references, it could be known that the stabilization problem of system (44) via controller (52) can be made between Corollary 3 in this article and some references 41,42 . However, it is said that the key idea of partially delay‐dependent controllers in such two references cannot be applied and should be revised to be u(t)=Kx(tτ).…”
Section: Numerical Examplementioning
confidence: 99%
See 2 more Smart Citations